Association of Voltage-Gated Potassium Channel Polymorphisms with the Risk and Prognosis of Epilepsy in the Saudi Population: A Case–Control Study - Mansour A. Alghamdi; Laith N. AL-Eitan; Mansour Y. Otaif; Doaa M. Rababa’h; Maryam K. Alasmar; Abdulaziz M. Al-Garni; Rayyh A. M. Saleh; Nawal F. Abdel Ghaffar (Medicina)
Background and Objectives: Epilepsy, known as an unprovoked seizure, arises from the human brain. Genetics plays a fundamental role in the development and progression of the disorder. This study aimed to investigate the influence of voltage-gated K+ channels on the risk of epilepsy. Materials and Methods: Several genetic variants were examined using PCR sequencing. This case–control study was conducted on 296 individuals who were diagnosed with epilepsy, in addition to 293 healthy participants. Results: This study revealed that within KCNAB1, both rs3755631 and rs4679773 are correlated with epilepsy, and the p-values = 0.04 for both allelic associations. In addition, regarding the KCNJ10 gene, we found that rs2820585, rs946420, rs1186679, rs61822012, and rs1186685 were significantly correlated with epilepsy risk (p-values = 0.034, 0.045, 0.021, 0.048, and 0.018), respectively. Conclusions: From the current study, we conclude that voltage-gated potassium channels can impact epilepsy risk and can also interfere with the prognosis of epilepsy.